2012
DOI: 10.1039/c1sm06421e
|View full text |Cite
|
Sign up to set email alerts
|

Wettability of silicananoparticle–surfactant nanocomposite interfacial layers

Abstract: The hydrophobicity of a particle surface can be tuned by the addition of surfactants that change the surface free energy for their attachment to a liquid interface. In this work, we report an experimental study where the wettability properties of silica nanoparticles are modified by the adsorption of alkyltrimethylammonium surfactants (C n TAB, n ¼ 12, 16) on the surface of the particles. We have pointed out that the wettability of the complexes is controlled by an intricate balance of electrostatic and hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
125
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 151 publications
(140 citation statements)
references
References 46 publications
14
125
1
Order By: Relevance
“…It was found that d = 9.0, 15.0, and 60.0 ± 0.2 nm, as average particle diameters, in agreement with the nominal values by the BET data, i.e., 300, 200, and 50 cm 2 /g, respectively, and a ζ-potential of −42 ± 4 mV, in agreement with what was found in ref 25.…”
Section: Methodssupporting
confidence: 89%
“…It was found that d = 9.0, 15.0, and 60.0 ± 0.2 nm, as average particle diameters, in agreement with the nominal values by the BET data, i.e., 300, 200, and 50 cm 2 /g, respectively, and a ζ-potential of −42 ± 4 mV, in agreement with what was found in ref 25.…”
Section: Methodssupporting
confidence: 89%
“…From the comparison of the latter two isotherms, it is apparent that the increase in the salinity of the solution results in an increase of the surface activity of CTAB at the air-water interface and in a noticeable decrease of the critical micellar concentration (cmc) of about one decade [29]. It is worth to mention that seawater contains a complex salt mixture [30], with NaCl as the major component.…”
Section: Effect Of Surfactant On the Sw Interfacial Propertiesmentioning
confidence: 99%
“…For this reason, the static contact angle (CA) tests of p‐SiO 2 and f‐SiO 2 were carried out and the results shown in the insets of Figure reveal that the CA values increase from 12° (p‐SiO 2 ) to 52° (f‐SiO 2 ). The hydrophobicity improvement of f‐SiO 2 suggests better dispersion and fine compatibility in polymer matrix …”
Section: Resultsmentioning
confidence: 99%